catena-Poly[[[dichloridozinc(II)]-mu-1,4-bis(1H-benzimidazol-2-yl- kappa N-3)butane]1,4-bis(1H-benzimidazol-2-yl)butane solvate] - Zhou, Y.L.; Zeng, M.H.; Ng, S.W. (International Union of Crystallography, 2010)
In the crystal structure of the title coordination polymer/co-crystal, {[ZnCl2(C18H18N4)]center dot C18H18N4}(n), the tetrahedrally coordinated Zn-II ions are linked by the N-heterocycle into a linear chain. Another N-heterocycle present is not coordinated to the metal atom but interacts with the chain through N-H center dot center dot center dot N and N-H center dot center dot center dot Cl hydrogen bonds. The butyl chain of the uncoordinated ligand is disordered over three positions in a 0.511 (4):0.289 (5):0.200 (5) ratio.